Os operadores argumentativos em textos do ensino médio: uma análise fenomenológica - SOUSA, Maria Goretti Barros Rocha de (2024)
The act of writing is a complex activity, composed of textual elements that allow the expression of ideas and arguments through language. These elements can be articulated among themselves through mechanisms of textual cohesion and coherence. In this scenario, this research is entitled “Argumentative Operators in High School Texts: a phenomenological analysis”. The main objective of the research is to “Analyze the argumentative operators present in dissertative-argumentative texts produced by high school students”. As a theoretical framework, we seek to base the research on the perspective of Textual Linguistics with authors who contribute significantly to this area of knowledge, such as Beaugrande and Dressler (1981), who define cohesion as the linguistic elements that connect parts of the text and coherence as the logical interpretation of the reader; Koch and Elias (2006) who discuss argumentative language and its relations with textual linguistics, Adam (2019) who defines argumentative connectors, as organizers and textual markers, offering a solid basis for understanding how these elements structure the text and construct meanings; and Marcuschi (2008), who explores textual production from cognitive and pragmatic perspectives, demonstrating how cohesive texts facilitate clear communication. Other theorists, such as Antunes (2005) and Cavalcante (2014), were also used to broaden the discussion on the theoretical foundations of the research. The methodological procedures were based on Merleau-Ponty's Phenomenology (2006), and for data collection, we chose to construct a corpus consisting of texts from 3rd grade high school students from a public school, the research investigation region. Data analysis was guided by the following question: How do high school students use argumentative operators as cohesive links in argumentative texts? The results found can significantly contribute to expanding studies on the use of argumentative operators in texts, offering support for improving Portuguese language teaching in public schools in Maranhão, in order to strengthen pedagogical practices focused on textual production.